Optimizing yield and quality in guava through crop regulation: comprehensive review (Indian Journal of Arid Horticulture, 2025)
Guava (Psidium guajava L.) is a prominent tropical and subtropical fruit crop valued for its high nutritional content, economic returns, and adaptability to diverse agro-climatic conditions. However, its productivity and fruit quality are often challenged by irregular flowering, excessive fruit set, and off-season bearing, which lead to small fruit size, poor market value, and high management costs. Crop regulation in guava is a critical agronomic strategy aimed at synchronizing flowering and fruiting, improving fruit quality, and enhancing overall profitability. This review consolidates existing knowledge on the various crop regulation techniques employed in guava cultivation, including mechanical methods (pruning and deblossoming), chemical treatments (application of growth regulators such as NAA, ethrel, and urea), and cultural practices (water stress, root exposure, and nutritional management). Each method is discussed with respect to its physiological basis, effectiveness under different environmental conditions, and impact on flowering intensity, fruit set, yield, and quality attributes. The role of innovative approaches such as the use of bio-regulators and precision horticulture is also explored to address emerging challenges in climate resilient guava production. Comparative evaluation of crop regulation strategies across different seasons—particularly in tropical regions where guava tends to bear multiple crops—provides insights into season-specific recommendations. Emphasis is also placed on integrating crop regulation with canopy management and varietal selection for maximizing resource-use efficiency. The review identifies key research gaps, including the need for region-specific standardization of practices, development of environmentally safe chemical alternatives, and deeper understanding of the molecular and hormonal mechanisms governing floral induction and abscission. This article aims to serve as a comprehensive reference for researchers, extension workers, and growers seeking sustainable solutions to enhance guava productivity and fruit quality through effective crop regulation practices.